Penerapan Penilaian Prinsip 5C Sebagai Upaya Pencegahan Pembiayaan Bermasalah di Bank Jateng Capem Juwana - Rokhmad Budiyono; Natoil Natoil; silvia hendrayanti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
Banks and non-bank financial institutions basically have a very strategic function and play a very important role in a country's economic activities. The existence of banks currently plays a very important role for the welfare of society. This study aims to determine the application of the 5C principle assessment (Character, Capacity, Capital, Collateral, Condition) as an effort to prevent problem financing at Bank Jateng Capem Juwana. The research method used in this research is Multiple Linear Regression Test, Partial Hypothesis Test (t test), Model Feasibility Test, Coefficient of Determination Test. The data used in this research is secondary data with a total of 98 respondents who are the research subjects. Based on the research results, the coefficient of determination is expressed in percentage. R2 values ​​range from 0 < R2 < 1 . In the SPSS output, the coefficient of determination lies in the Summaary Model and is written R Square, which means that the Financing Problem for Bank Jateng Juwana's Micro Service Unit is 83.2% influenced by Character, Capacity, Capital, Collateral, Condition. Bank Jateng, Juwana Micro Service Unit, should further explore the 5C principles in lending so that the quality of debtors is maintained and the prevention of problem financing is maintained. For future researchers, it is better to add other independent variables such as Personality, Prospect, Payment, Profitability, Protection and others to get more detailed and accurate results regarding the prevention of problem financing.Banks and non-bank financial institutions basically have a very strategic function and play a very important role in a country's economic activities. The existence of banks currently plays a very important role for the welfare of society. This study aims to determine the application of the 5C principle assessment (Character, Capacity, Capital, Collateral, Condition) as an effort to prevent problem financing at Bank Jateng Capem Juwana. The research method used in this research is Multiple Linear Regression Test, Partial Hypothesis Test (t test), Model Feasibility Test, Coefficient of Determination Test. The data used in this research is secondary data with a total of 98 respondents who are the research subjects. Based on the research results, the coefficient of determination is expressed in percentage. R2 values ​​range from 0 < R2 < 1 . In the SPSS output, the coefficient of determination lies in the Summaary Model and is written R Square, which means that the Financing Problem for Bank Jateng Juwana's Micro Service Unit is 83.2% influenced by Character, Capacity, Capital, Collateral, Condition. Bank Jateng, Juwana Micro Service Unit, should further explore the 5C principles in lending so that the quality of debtors is maintained and the prevention of problem financing is maintained. For future researchers, it is better to add other independent variables such as Personality, Prospect, Payment, Profitability, Protection and others to get more detailed and accurate results regarding the prevention of problem financing.